2014
DOI: 10.1186/1750-1326-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β causes excitotoxic neurodegeneration and multiple sclerosis disease progression by activating the apoptotic protein p53

Abstract: Background: Understanding how inflammation causes neuronal damage is of paramount importance in multiple sclerosis (MS) and in other neurodegenerative diseases. Here we addressed the role of the apoptotic cascade in the synaptic abnormalities and neuronal loss caused by the proinflammatory cytokines interleukin-1β (IL-1β) and tumor necrosis factor (TNF-α) in brain tissues, and disease progression caused by inflammation in relapsing-remitting MS (RRMS) patients. Results: The effect of IL-1β, but not of TNF-α, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 65 publications
2
47
0
Order By: Relevance
“…Microglia secretes cytokines, such as TNF-α and IL-1β, which have both been shown to promote neuronal damage when present in excessive amounts (Monif, et al, 2010, Rossi, et al, 2014). Our results showed that LPS suppressed TREM2 but increased TREML2 mRNA levels, thus promoting microglia to pro-inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia secretes cytokines, such as TNF-α and IL-1β, which have both been shown to promote neuronal damage when present in excessive amounts (Monif, et al, 2010, Rossi, et al, 2014). Our results showed that LPS suppressed TREM2 but increased TREML2 mRNA levels, thus promoting microglia to pro-inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…Congruently, an enhanced striatal neuron EPSC phenotype is correlated with neurodegeneration in EAE (10). CSF from MS patients increases EPSCs, along with signs of neuronal death, in mouse corticostriatal slice cultures; and this effect is mediated by IL-1b (78,79). In the cerebellum, IL-1b increases EPSCs in Purkinje cells during EAE by impairing glutamate clearance by astroglia in neuronal synapses, an effect which is blocked by an IL-1R antagonist (56).…”
Section: Il-1b Promotes Neurotoxicity In Eaementioning
confidence: 98%
“…Recent reports showed that sublethal MAC triggers NLRP3 (nucleotidebinding domain, leucine-rich repeat containing family, pyrin domain-containing 3) inflammasome activation and release of IL-1β (24,25). We therefore tested whether MAC regulates secondary inflammatory processes after TBI by inducing inflammasome activation in brain cells, leading to production of IL-1β, which is known to be toxic to neurons (26,27). In situ hybridization demonstrated expression of IL-1β mRNA in injured brains of controls at 72 h post-TBI.…”
Section: Cd59-2a-crig Reduces Inflammation Mitochondrial Stress Andmentioning
confidence: 99%